The search for delicious - Babbitt, Natalie (New York : Square Fish/Farrar, Straus and Giroux, 2007)
The Prime Minister is compiling a dictionary and when no one at court can agree on the meaning of delicious, the King sends his twelve-year-old messenger to poll the country.
5.4
5-8
5-8
Wilson's Children
Elem. School Library Collection
Library Journal
Keywords: Public opinion -- Juvenile fiction; Public opinion -- Fiction; Fantasy; Public opinion -- Fiction; Fantasy fiction